THE INCLUSION OF SPECIAL EDUCATION INTO PRESCHOOL AND ELEMENTARY GENERAL EDUCATION INSTITUCIONS IN LATVIA - Kūle, Ligita; Rajevska, Feliciana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The statistics of the Ministry of Education and Science show a positive dynamics in the availability of special education. However, for inclusion of children with special needs into the mainstream education, the provision of support staff (psychologist, speech therapist, special educator) is essential. The aim of this research is to investigate the national legislation on the inclusion of children with special needs in the pre-school and elementary school education system, exploring the funding aspect. The study analyses the legislative basis for the provision of special education in mainstream schools. The research investigated the provision of special education in general education institutions in Alūksne Municipality in September - December 2016 (case study) and carried out several interviews with field experts. The study is conducted in the context of theory of inclusive special education. The study shows that in providing education support staff in an educational institution in the framework of the existing public education and special education funding model and in the context of a rural region with a low population density, there is a need for a rational approach, careful planning and process management: gathering information about all pupils with special needs in a municipality, cooperation with parents, management and mobilization of all resources.